Pengaruh Strategi Pemasaran Terhadap Keputusan Pembelian Pada Apertemen Trilium Office And Residence Surabaya - Dionisius Aldio Manuhutu; Achmad Daengs GS; Sugiharto Sugiharto; Bambang Karnain; I Gde Wiyase (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
Introduction : The purpose of this study was to analyze the effect of product, price, promotion, and location either partially or simultaneously on the purchasing decision of the Trillium Residence Surabaya Apartment. Research Metodology : The research method used is descriptive quantitative. The sampling technique used was accidental sampling so that from the population a sample of 100 respondents was taken, the data collection method used was observation, questionnaires, and libraries. The analytical tool used in this research is SPSS version 25 software. The data analysis technique used is multiple linear regression, t test, F test and coefficient determination. Research Result : From the results of the analysis using the T test, F analysis of hypothesis testing at the confidence level α = 5%, the t value is 0.847 < t table 1.98 and the significant value is 0.752 > 0.05.it can be concluded that the product variable has no effect on purchasing decisions for the Trillium Residence Surabaya Apartment with, for hypothesis number two the calculated t value is 1.704 < t table 1.98 and the significance value is 0.092 > 0.05 the price does not affect the purchasing decision of the Trillium Residence Surabaya Apartment, for hypothesis number three, the calculated t value is 1.704 < t table 1.98 and the significance value is 0.092 > 0.05 the promotion variable affects the purchasing decision of the Trillium Residence Surabaya Apartment and the location affects the purchasing decision Trillium Residence Surabaya Apartment. Based on testing using the F test, f count value of 62,934 > F table of 2.70 and a significance value of 0.000 <0.05 it is proven that the product, price, promotion, and location variables simultaneously influence the purchasing decision of the Trillium Residence Surabaya Apartment.